Analysis of The Influence of Experiential Marketing on the Repurchase Intention of Daya Motor Consumers in Bandung - Suryahartanto, Geraldy; Susanto, Sani; Jane, Orpha (Jurnal Ekuisci, 2024)
In the era of increasingly intense competition in the two-wheeled automotive industry, particularly in the electric motorcycle segment in Indonesia, various challenges have emerged for industry players. PT Astra Honda Motor (AHM), one of the major players in this industry, faces additional challenges due to quality issues related to the eSAF frame, which have impacted its reputation and sales. As an official Honda dealer, Daya Motor must tackle these challenges by maintaining and enhancing its sales amidst tightening competition and negative perceptions of the product. This research analyzes the factors influencing consumer repurchase interest at Daya Motor, focusing on three main variables: experiential marketing, service quality, and customer satisfaction with Structural Equation Modeling. The research methodology includes evaluating the impact of experiential marketing and service quality on customer satisfaction and their effects on customer loyalty and repurchase interest. The results of this study reveal that Daya Motor's customer loyalty level is low. Furthermore, customer satisfaction does not always lead to customer loyalty.